Library Creation of Ultrasmall Multi‐metallic Nanoparticles Confined in Mesoporous MFI Zeolites. (14th May 2021) - Jia, Xiaoli; Jiang, Jingang; Zou, Shihui; Han, Lu; Zhu, Haiyin; Zhang, Qing; Ma, Yue; Luo, Peng; Wu, Peng; Mayoral, Alvaro; Han, Xinbao; Cheng, Jun; et al.
Abstract: The development of materials integrated with ultrasmall multi‐metal nanoparticles (UMMNs) and mesoporous zeolite is a considerable challenge in chemistry and materials science. We designed a trifunctional surfactant, in which the pyridyl benzimidazole in the hydrophobic tail generates the mesopores through π–π stacking; the diquaternary ammonium in the hydrophilic headgroup direct the formation of MFI zeolite sheets and the nitrogen atoms in the heterocyclic rings coordinate with various metal ions to form UMMNs confined in the zeolite matrix after calcination and reduction. A library of 56 UMMNs confined within both micropores and mesopores of MFI zeolites (MMZs) with 4 mono‐, 14 bi‐ and 38 tri‐metallic nanoparticles (sizes of 1.3–4.7 nm) of combinations of Rh, Pd, Pt, Au, Fe, Co, Ni, Cu and Zn were made. An improved catalytic performance was exhibited in the sequence of Rh‐MMZ<Rh/Pt‐MMZ<Rh/Pt/Ni‐MMZ for the mild oxidation of methane to methanol or liquid acid. Abstract : A library of ultrasmall multi‐metallic nanoparticles confined in both micro‐ and mesopores of molecular sieves was created by the trifunctional templating route.